2018
DOI: 10.5888/pcd15.170311
|View full text |Cite
|
Sign up to set email alerts
|

Population-Tailored Care for Homeless Veterans and Acute Care Use, Cost, and Satisfaction: A Prospective Quasi-Experimental Trial

Abstract: IntroductionAlthough traditional patient-centered medical homes (PCMHs) are effective for patients with complex needs, it is unclear whether homeless-tailored PCMHs work better for homeless veterans. We examined the impact of enrollment in a Veterans Health Administration (VHA) homeless-tailored PCMH on health services use, cost, and satisfaction compared with enrollment in a traditional, nontailored PCMH.MethodsWe conducted a prospective, multicenter, quasi-experimental, single-blinded study at 2 VHA medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Between 2012 and 2014, O’Toole and colleagues studied 2 VHA medical centers to assess health services use, cost, and satisfaction over 12 months for a cohort of 266 homeless Veterans. (22) They found that compared with PACT patients, HPACT patients had more social work visits (4.6 vs 2.7 visits) and fewer emergency department (ED) visits for ambulatory care-sensitive conditions (0 vs 0.2 visits); a significantly smaller percentage of Veterans in HPACT were hospitalized (23.1% vs 35.4%) or had mental health–related ED visits (34.1% vs 47.6%). They also found significant differences in primary care provider–specific visits (HPACT, 5.1 vs PACT, 3.6 visits), mental health care visits (HPACT, 8.8 vs PACT, 13.4 visits), 30-day prescription drug fills (HPACT, 40.5 vs PACT, 58.8 fills), and use of group therapy (HPACT, 40.1% vs PACT, 53.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Between 2012 and 2014, O’Toole and colleagues studied 2 VHA medical centers to assess health services use, cost, and satisfaction over 12 months for a cohort of 266 homeless Veterans. (22) They found that compared with PACT patients, HPACT patients had more social work visits (4.6 vs 2.7 visits) and fewer emergency department (ED) visits for ambulatory care-sensitive conditions (0 vs 0.2 visits); a significantly smaller percentage of Veterans in HPACT were hospitalized (23.1% vs 35.4%) or had mental health–related ED visits (34.1% vs 47.6%). They also found significant differences in primary care provider–specific visits (HPACT, 5.1 vs PACT, 3.6 visits), mental health care visits (HPACT, 8.8 vs PACT, 13.4 visits), 30-day prescription drug fills (HPACT, 40.5 vs PACT, 58.8 fills), and use of group therapy (HPACT, 40.1% vs PACT, 53.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Integrated primary care (IPC) models that address addiction and SDOH could promote primary care engagement and mitigate problematic patterns of acute care utilization. 8 10 IPC models utilize interdisciplinary teams to provide longitudinal, patient-centered care; reduce care fragmentation; and avert preventable hospitalizations via enhanced primary care access and disease management. 9 Such approaches have increased primary care utilization (especially preventive services) and reduced ED visits and hospitalizations for patients with chronic health conditions, serious mental illness, and experience of homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…This paper used responses from a survey of veterans (N=5,766) who experienced homelessness and were receiving primary care at 26 Department of Veterans Affairs, Veterans Administration (VA) Medical Centers in 2018. The parent study compared primary care experiences among those who used a new kind of VA clinic designed for homeless-experienced veterans (Homeless Patient−Aligned Care Teams) 14 and those receiving non−Homeless Patient−Aligned Care at the same VA Medical Centers.…”
Section: Methodsmentioning
confidence: 99%